Atomic level structural and chemical analysis of Cr-doped Bi₂Se₃ - Ghasemi, A; Kepaptsoglou, D; Collins-McIntyre, L; Ramasse, Q; Hesjedal, T; Lazarov, V (Nature Publishing Group, 2016)
We present a study of the structure and chemical composition of the Cr-doped 3D topological insulator Bi2Se3. Single-crystalline thin films were grown by molecular beam epitaxy on Al2O3 (0001), and their structural and chemical properties determined on an atomic level by aberration-corrected scanning transmission electron microscopy and electron energy loss spectroscopy. A regular quintuple layer stacking of the Bi2Se3 film is found, with the exception of the first several atomic layers in the initial growth. The spectroscopy data give direct evidence that Cr is preferentially substituting for Bi in the Bi2Se3 host. We also show that Cr has a tendency to segregate at internal grain boundaries of the Bi2Se3 film.